Disharmoni Regulasi Pencalonan Mantan Terpidana Korupsi Pada Pemilu DPRD Banten 2019–2024: Perspektif Peraturan Perundangan dan Hukum Progresif - Rio Taqy Fadillah; Ismail Marzuki (JURNAL USM LAW REVIEW, 2025)
This study aims to analyze the candidacy of former corruption convicts as members of the Banten Provincial DPRD in the 2019 and 2024 elections, emphasizing the disharmony of legal norms and its implications for democratic legitimacy. The method used is a normative juridical approach with a statutory approach, a conceptual approach, and a case approach, enabling a comprehensive analysis of regulations, court decisions, and practices in the field.  The results of the study show that in the 2019 elections, there was a contradiction between the Election Law, PKPU, and the Supreme Court Decision, which created legal uncertainty and opened up the possibility of former corruptors running for office without a strong ethical mechanism. In the 2024 elections, regulations are more structured through the Constitutional Court Decision and PKPU 10/2023, but their implementation still faces challenges in the form of weak factual supervision of candidates' track records, the dominance of political parties' electoral interests, and low commitment to political ethics. The novelty of this research lies in the integration of regulatory analysis with a progressive legal perspective to assess the legitimacy of local democracy. This study recommends the establishment of an independent political ethics institution, the reformulation of stricter candidacy norms, and the strengthening of political party codes of ethics as practical steps to ensure a cleaner, more accountable, and dignified electoral democracy.    Penelitian ini bertujuan untuk menganalisis pencalonan mantan terpidana korupsi sebagai anggota DPRD Provinsi Banten pada Pemilu 2019 dan 2024, dengan menekankan disharmoni norma hukum serta implikasinya terhadap legitimasi demokrasi. Metode yang digunakan adalah normative juridical approach dengan pendekatan perundang-undangan (statute approach), konseptual (conceptual approach), dan kasus (case approach), sehingga memungkinkan analisis komprehensif antara regulasi, putusan peradilan, dan praktik di lapangan. Hasil penelitian menunjukkan bahwa pada Pemilu 2019 terjadi kontradiksi antara UU Pemilu, PKPU, dan Putusan MA yang menimbulkan ketidakpastian hukum dan membuka ruang pencalonan mantan koruptor tanpa mekanisme etik yang kuat. Pada Pemilu 2024, regulasi lebih terstruktur melalui Putusan MK dan PKPU 10/2023, namun penerapannya masih menghadapi tantangan berupa lemahnya pengawasan faktual terhadap rekam jejak calon, dominannya kepentingan elektoral partai politik, dan rendahnya komitmen etika politik. Kebaruan penelitian ini terletak pada integrasi analisis regulasi perundang-undangan dengan perspektif hukum progresif untuk menilai legitimasi demokrasi lokal. Penelitian ini merekomendasikan pembentukan lembaga etik politik independen, reformulasi norma pencalonan yang lebih ketat, serta penguatan kode etik partai politik sebagai langkah aplikatif untuk memastikan demokrasi elektoral yang lebih bersih, akuntabel, dan bermartabat.